Chemical Synthesis Elucidates the Immunological Importance of a Pyruvate Modification in the Capsular Polysaccharide of Streptococcus pneumoniae Serotype 4. Issue 34 (24th July 2015) - Pereira, Claney L.; Geissner, Andreas; Anish, Chakkumkal; Seeberger, Peter H.
Abstract: Carbohydrate modifications are believed to strongly affect the immunogenicity of glycans. Capsular polysaccharides (CPS) from bacterial pathogens are frequently equipped with a pyruvate that can be placed across the 4, 6‐, 3, 4‐, or 2, 3‐positions. A trans‐2, 3‐linked pyruvate is present on the CPS of the Gram‐positive bacterium Streptococcus pneumoniae serotype 4 (ST4), a pathogen responsible for pneumococcal infections. To assess the immunological importance of this modification within the CPS repeating unit, the first total synthesis of the glycan was carried out. Glycan microarrays containing a series of synthetic antigens demonstrated how antibodies raised against natural ST4 CPS specifically recognize the pyruvate within the context of the tetrasaccharide repeating unit. The pyruvate modification is a key motif for designing minimal synthetic carbohydrate vaccines for ST4. Abstract : Unusually Protective : In the search for a glycan epitope for protection against Streptococcus pneumoniae serotype 4, total synthesis of the repeating unit (see structure) enabled the identification of pyruvate as a crucial determinant of immunogenicity. This lays the foundation for the development of a new antibacterial vaccine candidate against Streptococcus pneumoniae serotype 4.